2013
DOI: 10.1002/stem.1426
|View full text |Cite
|
Sign up to set email alerts
|

Hes1 Desynchronizes Differentiation of Pluripotent Cells by Modulating STAT3 Activity

Abstract: Robust development of the early embryo may benefit from mechanisms that ensure that not all pluripotent cells differentiate at exactly the same time: such mechanisms would build flexibility into the process of lineage allocation. This idea is supported by the observation that pluripotent stem cells differentiate at different rates in vitro. We use a clonal commitment assay to confirm that pluripotent cells commit to differentiate asynchronously even under uniform differentiation conditions. Stochastic variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…Zap70 KD results in not only severe defects with retinoic acid treatment in vitro but also defective teratoma formation in vivo [57]. By enhancing Stat3 activity, Hes1 also delays mESC differentiation [58]. Consistently, our results demonstrated that upregulation of Stat3 resulted in severe developmental defects, whereas when Stat3 was knocked down with siStat3 or when Stat3 activation was selectively inhibited, the Pwp1 KD cells regained their differentiation potential.…”
Section: Stem Cellssupporting
confidence: 83%
“…Zap70 KD results in not only severe defects with retinoic acid treatment in vitro but also defective teratoma formation in vivo [57]. By enhancing Stat3 activity, Hes1 also delays mESC differentiation [58]. Consistently, our results demonstrated that upregulation of Stat3 resulted in severe developmental defects, whereas when Stat3 was knocked down with siStat3 or when Stat3 activation was selectively inhibited, the Pwp1 KD cells regained their differentiation potential.…”
Section: Stem Cellssupporting
confidence: 83%
“…The LIF/STAT3 signaling pathway has been reported to be essential for maintaining the self‐renewal and pluripotency of mouse ESCs. Active STAT3 can target ESC self‐renewal‐ and differentiation‐related genes, whereas HES1 can enhance STAT3 activity and delay mouse ESC differentiation . LncRNAs, with rich information and diverse regulatory mechanisms, have been demonstrated as important epigenetic regulators in maintaining mouse ESC pluripotency .…”
Section: Discussionmentioning
confidence: 99%
“…Active STAT3 can target ESC selfrenewal-and differentiation-related genes, 22 whereas HES1 can enhance STAT3 activity and delay mouse ESC differentiation. 20 LncRNAs, with rich information and diverse regulatory mechanisms, have been demonstrated as important epigenetic regulators in maintaining mouse ESC pluripotency. 5 However, whether lncRNAs directly target the LIF/STAT3 signaling pathway and regulate ESC differentiation needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations